Brain storms : the race to unlock the mysteries of Parkinson's Disease - Palfreman, Jon (Scientific American / Farrar, Straus and Giroux, 2015)
"Seven million people worldwide suffer from Parkinson's-- with sixty thousand new cases diagnosed each year in the U.S. alone-- and it remains an enigma, with doctors, researchers, and patients hunting for a cure. In Brain Storms, award-winning journalist Jon Palfreman tells their story, a story that takes on urgency when he is diagnosed with the debilitating illness. Palfreman chronicles how scientists have labored to crack the mystery of what was once called 'the shaking palsy,' from the earliest clinical descriptions to the cutting edge of molecular neuroscience. He charts the victories and setbacks of a massive international effort to best the disease, referred to as one of the best windows into the brain itself."--